TRANSINTERNALISASI NILAI-NILAI KEPESANTRENAN MELALUI KONSTRUKSI BUDAYA RELIGIUS DI SEKOLAH - Muhammad Mushfi El Iq Bali; Susilowati Susilowati (Jurnal Pendidikan Agama Islam, 2019)
This paper aims to analyze students' moral decadence problems in school. Brawls, free sex and narcotics on students is evidence of school failure in building the religious character of students. One of the educational institutions that have succeeded in building the religious character of students is pesantren. This success was proven by a little reporting of deviant behaviour among santri. By using descriptive qualitative methods, researchers want to reveal the profile of public schools that not only excellent academic achievement but are also able to produce students who have a religious culture so as to avoid various deviant behaviours. The religious culture is formed through the internalization of the values of the pesantren, namely to incorporate Islamic values through habituation manifested in school programs like a pesantren. The implication of this study is to internalize the value of pesantren in schools that can shape the religious character of students. Students can avoid bad behaviour.